Thermochronometry of metamorphic rock complexes on the SE Peloponnese, Greece, using thermoluminescence (TL): preliminary experiments - Kanavou, Vasiliki; Athanassas, Constantin; Stamoulis, Konstantinos; Aslanoglou, Xenophon; Mouslopoulou, Vasiliki (HNPS Advances in Nuclear Physics, 2022)
Here, we report preliminary results from thermoluminescence (TL) measurements on metamorphic quartz from the SE Peloponnese, Greece, and we discuss its potential for thermometric and, possibly, thermochronometric applications over longer geological periods. Extensive high pressure/low temperature (HP/LT) schists associated with a 24 Ma metamorphic age, and with cooling ages ranging between 6-14 Ma (based on fission-track and (U-Th)/He thermochronometry), encompass sizable quartzite outcrops associated with substantially low radiation (U, Th, K concentrations below the analytical detection limits), allowing TL signal to grow on longer geological timescales. Although deeper TL traps (>360°C) appeared saturated as expected, geologically stable traps lying between around 360°C were found to be far from saturation. Once higher analytical resolution is achieved in the determination of the radioelement concentrations the recovered equivalent doses will be combined with the respective dose rates to explore the suitability of TL from quartz for longer-range thermochronometry in extremely low-radiation geological environments.